2001
DOI: 10.1046/j.1471-4159.2001.00184.x
|View full text |Cite
|
Sign up to set email alerts
|

Activation of 5‐HT1A but not 5‐HT1B receptors attenuates an increase in extracellular dopamine derived from exogenously administered l‐DOPA in the striatum with nigrostriatal denervation

Abstract: In order to determine whether L-DOPA-derived extracellular dopamine (DA) in the striatum with dopaminergic denervation is affected by activation of serotonin autoreceptors (5-HT 1A and 5-HT 1B receptors), we applied in vivo brain microdialysis technique to 6-hydroxydopamine-lesioned rats and examined the effects of the selective 5-HT 1A receptor agonist 8-hydroxy-2-(di-n-propylamino)tetralin (8-OH-DPAT) and the selective 5-HT 1B receptor agonist CGS-12066 A on L-DOPA-derived extracellular DA levels. Single L-D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
100
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(105 citation statements)
references
References 41 publications
4
100
1
Order By: Relevance
“…However, there is no compelling evidence from experimental models (Ahlenius and Salmi 1995) that selective engagement of 5-HT 1A receptors exerts clinically meaningful antiparkinson actions or that 5-HT 1A receptors are involved in the antiparkinson profiles of drugs evaluated herein. Furthermore, 5-HT 1A agonists exert a complex influence upon locomotor behavior and blunt DA release in the striatum (Barnes and Sharp, 1999;De La Garza and Cunningham, 2000;Millan, 2000): they also attenuate L-DOPA-induced DA release in the striatum from serotonergic neurons bearing 5-HT 1A autoreceptors (Arai et al, 1996;Kannari et al, 2001). These observations, together with the low activity at 5-HT 1A receptors of clinically effective antiparkinson agents, such as pramipexole, indicate that their stimulation is neither necessary nor sufficient for treatment of Parkinson's disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is no compelling evidence from experimental models (Ahlenius and Salmi 1995) that selective engagement of 5-HT 1A receptors exerts clinically meaningful antiparkinson actions or that 5-HT 1A receptors are involved in the antiparkinson profiles of drugs evaluated herein. Furthermore, 5-HT 1A agonists exert a complex influence upon locomotor behavior and blunt DA release in the striatum (Barnes and Sharp, 1999;De La Garza and Cunningham, 2000;Millan, 2000): they also attenuate L-DOPA-induced DA release in the striatum from serotonergic neurons bearing 5-HT 1A autoreceptors (Arai et al, 1996;Kannari et al, 2001). These observations, together with the low activity at 5-HT 1A receptors of clinically effective antiparkinson agents, such as pramipexole, indicate that their stimulation is neither necessary nor sufficient for treatment of Parkinson's disease.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the neurotoxin 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine, which depletes nigrostriatal pools of dopamine (DA) and induces a Parkinson's disease-like syndrome, reduces striatal levels of 5-HT (Pérez-Otañ o et al, 1991). Third, the antiparkinson agent and DA precursor L-dihydroxyphenylacetic acid (L-DOPA) displaces 5-HT from serotonergic neurons innervating the striatum, wherein it is transformed into DA (Arai et al, 1996;Kannari et al, 2001). Fourth, actions of antiparkinson agents at 5-HT receptors ) may participate in their influence upon the motor, mood, and cognitive symptoms of Parkinson's disease, although serotonergic properties do not underlie their ability to restore motor function per se (see Discussion).…”
mentioning
confidence: 99%
“…In line with the higher sensitivity of STN-HFS to inhibit 5-HT release in the PFC compared to the HIPP, the attenuation of L-DOPAinduced DA release by STN-HFS was more pronounced in the PFC. The inhibitory effect of STN-HFS on DA release could be related to its inhibitory action on 5-HT neuronal activity, because L-DOPA-induced DA release from striatal 5-HT terminals is sensitive to 8-OHDPAT, presumably through a reduction of 5-HT firing rate (Kannari et al, 2001;Carta et al, 2007). Recently, it has been shown that STN-HFS prolonged the increase in DA levels induced by L-DOPA in the striatum without affecting the magnitude of its effect (Lacombe et al, 2007).…”
Section: L-dopa and Stn-hfs Inhibit 5-ht Release Via Distinct Mechanismsmentioning
confidence: 99%
“…In PD, the loss of the DA transporter (DAT) most likely impairs its ability to maintain DA bioavailability, yet most studies indicate motor symptoms are seen only when ∼70% of striatal DAT is lost (Bernheimer et al, 1973;Bezard et al, 2001), indicating an alternate mechanism through which DA may still be effective to produce normal locomotion. Indeed, many studies have concluded that serotonergic terminals may transport L-DOPA or DA, and subsequently release DA to maintain DA signaling, albeit in a dysregulated fashion (Arai et al, 1995;Miller and Abercrombie, 1999;Tanaka et al, 1999;Kannari et al, 2001;Carta et al, 2007). However, it is a comparatively neglected observation that in sparsely dopaminergic innervated regions, such as the frontal cortex, the norepinephrine (NE) transporter (NET) can also transport DA (Moron et al, 2002) and NE uptake inhibitors, which can result in increased extracellular DA levels within the prefrontal cortex (Carboni et al, 1990;Di Chiara et al, 1992;Gresch et al, 1995;Tanda et al, 1997;Yamamoto and Novotney, 1998;Wayment et al, 2001;Masana et al, 2012).…”
Section: Introductionmentioning
confidence: 99%